Sentiment-Integrated Hybrid Valuation Model for Early-Stage Fintech Startups: Quantifying Hype Cycle Effects in Emerging Markets - Chaudhuri, Aditya (Digital Repository of Theses, 2026)
This dissertation develops and empirically validates a sentiment-integrated hybrid valuation model for early-stage FinTech startups in emerging markets. Traditional valuation methods struggle with early-stage companies due to absent financials, high uncertainty, and asymmetric information. While qualitative and hybrid approaches have emerged, they systematically exclude quantifiable sentiment metrics despite extensive evidence that investor psychology drives startup valuations. This research addresses three critical gaps: (1) the absence of operationalized hype cycle theory in startup valuation, (2) the lack of systematic integration of measurable sentiment indicators, and (3) limited understanding of sector-specific dynamics in FinTech. Using a sample of 113 funding rounds from 68 companies across India and emerging markets (2022-2025), this study operationalizes the Gartner Hype Cycle through temporal phase analysis and quantifies public sentiment using Google Trends data. Hierarchical regression analysis reveals four key findings. First, companies securing funding during the recovery period (2024-2025) achieve 90% higher valuations than correction-period peers (2022-2023), providing empirical validation of hype cycle effects (p<0.001). Second, the sentiment-integrated hybrid model explains 48.9% of valuation variance—a 551% improvement over traditional demographic models (7.5% R²). Third, composite hype indicators outperform simple search volume metrics, though funding amount remains the dominant predictor. Fourth, FinTech companies exhibit heightened hype sensitivity due to regulatory uncertainty and technological complexity. This research makes three contributions: theoretical (integrating behavioral finance with private market valuation), methodology (operationalizing hype cycles with Google Trends), and practical (providing timing guidance for entrepreneurs and investors). A robustness check using 500 independent funding rounds confirms findings generalize beyond the original sample, with recovery premiums ranging from 50-90% depending on company maturity and geographic context.